Поховальні комплекси зі зброєю могильника Острів (за матеріалами археологічних досліджень 2017—2019 рр.) - Баранов, В.І.; Івакін, В.Г. (Археологія і давня історія України, 2020)
Стаття присвячена похованням зі зброєю, виявленим на західно-балтському некрополі Острів у 2017—2019 рр. Розглядаються типи озброєння та їх тактичне застосування. In 2017 the new burial ground on the right bank of Ros river between Puhachivka and Ostriv villages, in Rokytne district, Kyiv region was discovered. During 2017—2019 67 burials have been excavated there. Diverse and spectacular archaeological objects discovered during excavations — the spiral torques, crossbow ladder fibulae of type Bliujiene V, penannular brooches with rolled terminals, poppy-head terminals, funnel-shaped terminals, star-shaped terminals and widening terminals, bracelets with zoomorphic terminals, chains, temporal-rings and rings — all these grave goods are typical to Western Baltic tribes (Old Prussians, Curonians, Skalvians).